Kinetic model in the agglomeration design: on the example of Lviv - Habrel, Mykola; Kosmii, Mykhailo; Habrel, Mykhailo; Kovalchuk, Inna (Landscape Architecture and Art, 2023)
The kinetic components of local settlement systems with implemented processes related to the movement of people, materials, energy, information, etc. are studied. A kinetic model of the organization and controlled development of local settlement systems is proposed, which is built on the knowledge of movement theories and the properties of space associated with them and provides an opportunity to organize connections between its subsystems and elements of various spheres. The nature of kinetics (movement) in urbanized systems is concentrated in the systems’ processes, events, and behavior. Their study and modeling are accompanied by the analysis of phenomena that occur from the point of view of time (presented in the form of a function where time is independent), as well as random events, which by their nature are poorly predicted. The provisions of the kinetic model are applied to the analysis, evaluation, and justification of the concept of spatial organization and development of the local settlement system "Great Lviv". The prospects of Lviv as an agglomeration in the system of connections and relations with the environment are revealed. The requirements for development and conceptual proposals for the optimization of movement within the agglomeration are substantiated. It is defined that requirements and proposals should be oriented toward the search for solutions that reveal the uniqueness of the city space and its surroundings, ensure the harmonious integrity of the agglomeration, and the practical "mounting" of communication functions into the structure of the space.